Correction: Towards efficient initiators for two-photon induced polymerization: fine tuning of the donor/acceptor properties. Issue 2 (12th March 2019) - Holzer, Brigitte; Lunzer, Markus; Rosspeintner, Arnulf; Licari, Giuseppe; Tromayer, Maximilian; Naumov, Sergej; Lumpi, Daniel; Horkel, Ernst; Hametner, Christian; Ovsianikov, Aleksandr; Liska, Robert; Vauthey, Eric; et al.
Abstract : Correction for 'Towards efficient initiators for two-photon induced polymerization: fine tuning of the donor/acceptor properties' by Brigitte Holzer et al., Mol. Syst. Des. Eng., 2019, DOI: ;10.1039/c8me00101d .